The Great Bridge of China? Journalism Education Curriculum Trends Suggest More Research Into the Capacity for International Mobility Among Chinese Journalism Graduates - Cokley, John; Jianlin, Wen; Yanling, Liu; Wenshuai, Xie (Journalism & mass communication educator, 2019)
Current curriculum trends in tertiary journalism and communication education in the People’s Republic of China are investigated using information from the websites of the 2,198 Chinese universities that published course lists in December 2013. Of those, 439 offered journalism majors and this article samples 274 of those universities (12.5% of the national total). They fall into four groups: Research-oriented, Research and Teaching, Teaching only, and Specialized. A content analysis is conducted of subject synopses published on each university’s website. While international research suggests that subject offerings are likely to reflect a combination of internal institutional policies regarding journalism education and domestic student demand, with some external influence from government, educational institutions, and employer requirements, only in China is there evidence that journalism courses include compulsory study of a major global foreign language specifically for journalists (in this case, English). This study suggests further investigation into whether Chinese journalism graduates will have more capacity to be globally mobile and thus more employable than contemporary graduates from Europe, the United States, the United Kingdom, and Australia.